Spin-orbital entanglement and the breakdown of singlets and triplets in Sr 2RuO 4 revealed by spin- and angle-resolved photoemission spectroscopy - Veenstra, C. N.; Haverkort, Maurits W. (Physical review letters, 2014)
Spin-orbit coupling has been conjectured to play a key role in the low-energy electronic structure of Sr2RuO4. By using circularly polarized light combined with spin- and angle-resolved photoemission spectroscopy, we directly measure the value of the effective spin-orbit coupling to be 130±30 meV. This is even larger than theoretically predicted and comparable to the energy splitting of the dxy and dxz,yz orbitals around the Fermi surface, resulting in a strongly momentum-dependent entanglement of spin and orbital character in the electronic wavefunction. As demonstrated by the spin expectation value ⟨→sk⋅→s−k⟩ calculated for a pair of electrons with zero total momentum, the classification of the Cooper pairs in terms of pure singlets or triplets fundamentally breaks down, necessitating a description of the unconventional superconducting state of Sr2RuO4 in terms of these newly found spin-orbital entangled eigenstates.
Die Ziffern 2 und 4 im Titel sind tiefgestellt
Gesehen am 27.09.2017